2020
DOI: 10.1111/age.13011
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variation in HOXB7 and HOXB8 involves in the formation of beard trait in chickens

Abstract: The derived feathering phenotype beard in domestic birds is an ideal resource to investigate the genetic mechanisms controlling feather development and differentiation. In the present study, we performed a GWAS and QTL linkage analysis on the trait of beard in Beijing fatty chicken. One major QTL (1.2-1.9 Mb) was identified that could explain 34% of the phenotypic variation. The copy number variation that was copied from the region (GGA27:3 578 409-3 592 890 bp) containing homebox B7 (HOXB7) and homebox B8 (HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…YOU chicken is a Chinese native breed with special appearance characteristics, including crests, beards, feathered legs, and polydactyly. Recently, Yang et al (2020) deciphered that the copy number variation in HOXB7 and HOXB8 is responsible for the beard trait, which coincides exactly with the CNV detected in our study, especially exhibiting two copy number increase in YOU chicken.…”
Section: Discussionsupporting
confidence: 88%
“…YOU chicken is a Chinese native breed with special appearance characteristics, including crests, beards, feathered legs, and polydactyly. Recently, Yang et al (2020) deciphered that the copy number variation in HOXB7 and HOXB8 is responsible for the beard trait, which coincides exactly with the CNV detected in our study, especially exhibiting two copy number increase in YOU chicken.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, a duplicated sequence close to the first intron of SOX5 has been linked to the peacomb phenotype [Wright et al, 2009], while an inverted duplication including EDN3 is associated with dermal hyperpigmentation in chicken [Dorshorst et al, 2011]. In addition, partial duplication of PRLR has been related to late feathering [Elferink et al, 2008], whereas a CNV linked with the HOXB7 and HOXB8 genomic region has been associated with the beard phenotype [Yang KX et al, 2020] in chicken.…”
Section: Development and Application Of Snp Arrays For The Assessment...mentioning
confidence: 99%
“…Previously, a GWAS performed on the Beijing fatty chicken showed that the copy number variations in the homeobox B7 ( HOXB7 ) and homeobox B8 ( HOXB8 ) genes were involved in forming beard traits [ 30 ]. While in goats, evaluating the beard traits has been carried out in some goat breeds in Southwest China recently [ 2 ], but no previous studies have so far investigated the goat beard traits by genome selection approach.…”
Section: Resultsmentioning
confidence: 99%